Kajlan Upaya Pengembangan Ramuan Battra Di Kabupaten Kutai Kartanegara - Widowati, Lucie; Murniwati, Murniwati (Jurnal Kefarmasian Indonesia, 2009)
The growth of the number of Traditional Healers at Kutai Kartanegara Regency increases, including the Traditional Healer of remedies, using medicinal plants. The presence of herbs Traditonal Healers indirectly in improving helath and this condition needs to be proved by a survey to Traditional Healers with remedies of medicinal plant, using a questionnaire instrument. Traditoonal Healers profiles obtained from interviews using a questionnaire that describes Traditional Healers characteristics, source of knowledge, permission practices, place / space of practice, patient records etc. It is of concern is that almost all Traditional Healers not yet registered with the local Ministry of Health and have no record of the patient. While in the case of the medicinal plants used by Traditional Healers, problems that arise are very varied although for medicinal plants / complaints / same disease. Rationally number of medicinal plants, how making the right ingredients, dosage of medication use and how long to use these medicinal plants, needs to be studied to assure safety of use and provide the expected properties. The assessment results will be the direction of further development is still traditionally used or will be carried out research into herbal standardized, phytopharmaca,even into the drug with the specific active compounds, so that can be directed to the acquisition of patents. In the framework of guidance covering the above matters, suggested the existence of cooperation and coordination with the Faculty of Medicine Faculty of Pharmacy, or who are in the province of East Kalimantan.